Factors influencing clinical breast cancer screening: A cross-sectional study among Islamic women in Kumasi Metropolis of Ghana - Abdul-Karim Abubakari; Janet Gross; Emmanuel Adusei-Poku (PLoS ONE, 2025)
Clinical breast cancer screening among Ghanaian women is generally unsatisfactory due to poor knowledge despite its critical role in the early detection of breast cancer. Available studies in Ghana show that Islamic women have poorer screening rates which may be due to sociocultural and religious barriers. Understanding the factors that influence clinical breast cancer screening among Islamic women is a critical step that can help the design of initiatives to increase screening among Muslim populations in Ghana. Therefore, this study aimed to explore the factors influencing clinical breast cancer screening among Islamic women in the Kumasi Metropolis of Ghana. From August 20, 2024, to November 01, 2024, a community-based cross-sectional systematic sampling technique was deployed in the Aboabo and Asawase communities of the Ashanti Region to select 500 Islamic women for the study. Binary logistic regression was employed to determine the relationships between variables. Outcome variables with P-values < 0.05 were considered statistically significant. Most of the respondents were of Ghanaian Northern ancestry, with secondary-level education as the highest educational attainment. Compared to women with low cultural and religious norms, women with stronger personal and religious norms had 0.61 lower odds of screening (aOR=0.61, 95% CI = 0.34–1.08). Participant’s level of religiosity had a significant association with clinical breast cancer screening, with 1.16 times higher odds of screening (aOR= 1.16, 95% CI = 1.02–1.32) after adjusting for the covariates. Islamic women perceived high benefits of clinical breast cancer screening but fear of personal and social norm violations at the screening centers and poor knowledge about breast cancer limited their actual participation in clinical breast cancer screening practices. Implementing a national breast cancer education campaign to emphasize the need for asymptomatic or routine screening and provider training on culturally competent practices is encouraged.